The Relationship Between Oral Health Knowledge And Oral Health Behavior Among Students Of Sman 1 Kerinci Kanan - Arunda Prastio; Ivan Arie Wahyudi; Prayudha Benni Setiawan (Sean Institute, 2023)
Based on basic health research in 2018, the percentage of dental and oral problems in Indonesia is relatively high, namely 57.6%. One of the groups is prone to dental and oral health problems in adolescents. Knowledge and behavior influence and play an important role in dental and oral health directly. The purpose of this study was to determine the relationship between oral health knowledge and oral health maintenance behaviors in students aged 15 – 18 at SMAN 1 Kerinci Kanan, Siak Regency, Riau Province. The cross-sectional study was conducted on 192 students in grades 10 – 12 using a random sampling method. The research instrument used questionnaires regarding oral health knowledge and behaviors that have been tested for validity and reliability. The analysis used to see the relationship between oral health knowledge variables and oral health behavioral behaviors in the study subjects was carried out using the Spearman Rank correlation technique (p < 0.05). The results of the study obtained 74% of students had good oral health knowledge and 59.9% had sufficient oral health behaviors. The results of the Spearman Rank test obtained that a p-value of 0.017 which (p < 0.05) and the Spearman correlation coefficient showed a positive value of 0.172. Conclusion: there is a significant relationship between oral health knowledge variables and oral health behaviors in students of SMAN 1 Kerinci Kanan, Siak Regency, Riau Province. The better the oral knowledge possessed, the better the oral health maintenance